Joyride : [large type] a memoir - Orlean, Susan (Thorndike Press large print biographies and memoirs., 2025)
"'The story of my life is the story of my stories,' writes Susan Orlean in this extraordinary, era-defining memoir from one of the greatest practitioners of narrative nonfiction of our time. Joyride is a magic carpet ride through Orlean's life and career, where every moment holds the potential for wonder. She takes us through her process of dreaming up ideas, managing deadlines, connecting with sources, chasing every possible lead, confronting writer's block, and crafting the perfect lede. Infused with Orlean's signature warmth and wit, Joyride is a must-read for anyone who hungers to start, build, and sustain a creative life"--